Device and composition in the Greek epic cycle - Sammons, Benjamin (Oxford University Press, 2017)
Benjamin Sammons argues that the poems of the so-called 'Epic Cycle' were constructed using the same traditional devices as the Homeric epics. From this insight he sheds new light on the overall form of these lost poems and offers fresh interpretation of the few remaining fragments